Outcome of surgical and radiation therapy treatment of grade II meningiomas: A single institution experience - Jia-Mahasap, Bongkot; Angkurawaranon, Salita; Suwansirikul, Songkiet; Chakrabandhu, Somvilai; Klunklin, Pitchayaponne; Onchan, Wimrak; Sripan, Patumrat; Chitapanarux, Imjai (Biomedical Sciences and Clinical Medicine, 2018)
Objective To evaluate local control and survival rates with two different treatment modalities: surgery alone and surgery plus adjuvant radiation therapy (RT). Methods Cases of 104 patients diagnosed with grade II meningiomas between 2004 and 2014 were retrospectively reviewed. Of those, 68 patients had complete medical records. For inclusion in this study, we required a follow-up period of more than 2 years. Age at diagnosis, initial tumor size, tumor location, extent of resection and adjuvant RT were categorized to identify possible parame-ters that may have affected the outcome of this disease. Result Thirty-seven patients (54%) received surgery alone while 31 patients (46%) received adjuvant RT. The 2-year and 5-year rates of local control (LC) were 94% and 87%, respectively. No correlation was found between other parameters and recurrence of tumors. Patients in our study who received adjuvant RT had significant lower overall survival rate (p=0.044). The 2-year overall survival (OS) was 99% and 5-year OS was 93%. Conclusion Tumor control and survival were found to be excellent in this retrospective study. Adjuvant RT did not influence local control, but was statistically associated with lower survival rates. Further prospective study should be performed to clarify the management of grade II meningiomas.